Coronavirus Anxiety Scale: A New Instrument to Measure Anxiety Symptoms Associated with COVID-19 - González-Rivera, Juan Aníbal (2020)
Background: The purpose of this study was to adapt and validate the Coronavirus Anxiety Scale in a sample of Hispanic residents in Puerto Rico. This instrument is a brief mental health screening to identify anxiety symptoms associated with COVID-19. Method: An availability sampling and a sample of 327 Spanish-speaking participants were used. Results: Psychometric analyses confirmed that the scale has a one-dimensional structure and solid reliability (Ω = .93) and validity. The five items met fair discrimination values, demonstrating that the instrument can distinguish between people with anxiety symptoms associated with COVID-19 and those without symptoms. According to the analyses performed, the cut-off points to identify significant symptoms of coronavirus anxiety was ≥ 10. The prevalence of significant symptoms of coronavirus anxiety was 15.29% (n = 50). Conclusions: These results support the scale as a useful and valid tool for clinical research and practice.